Supervisi Akademik Oleh Kepala Sekolah Dasar Untuk Mendorong Independent Learning Siswa Berdasarkan Kajian Systematic Literature Review - Barquna Tri Raraswati; Rahmania Utari (Universitas Negeri Malang, 2025)
Abstract: This study aims to analyze the role of principals in establishing a culture of academic supervision to strengthen teachers’ pedagogical competence and encourage students’ independent learning. The research adopts a systematic literature review method by collecting, selecting, and analyzing relevant articles published between 2020 and 2025 in Indonesian and English. The reviewed studies focus on principals’ practices in supervising teaching processes, including lesson planning, classroom observation, feedback, and professional development. The findings indicate that structured and reflective supervision contributes significantly to improving teachers’ ability in planning, implementing, and evaluating learning. Teachers who receive continuous guidance from principals demonstrate progress in using varied methods, media, and evaluation strategies, leading to better learning outcomes. Furthermore, improved pedagogical competence has an indirect impact on students’ independent learning, as teachers are more capable of designing lessons that promote autonomy and active engagement. The study concludes that the principal’s leadership in fostering a culture of academic supervision is crucial for both teacher development and student learning independence. Keywords: Principal; Academic Supervision; Pedagogical Competence; Independent Learning. Abstrak: Penelitian ini bertujuan untuk menganalisis peran kepala sekolah dalam membangun budaya supervisi akademik untuk meningkatkan kompetensi pedagogik guru sekaligus mendorong kemandirian belajar siswa. Metode yang digunakan adalah kajian literatur sistematis dengan menyeleksi dan menelaah artikel yang terbit antara tahun 2020 hingga 2025 dalam bahasa Indonesia maupun Inggris. Kajian difokuskan pada praktik kepala sekolah dalam melaksanakan supervisi pembelajaran, mencakup perencanaan, observasi kelas, pemberian umpan balik, serta pembinaan profesional guru. Hasil penelitian menunjukkan bahwa supervisi yang terstruktur dan reflektif mampu meningkatkan kemampuan guru dalam merancang, melaksanakan, dan mengevaluasi pembelajaran. Guru yang mendapat bimbingan berkelanjutan dari kepala sekolah menunjukkan peningkatan dalam pemilihan metode, media, dan evaluasi pembelajaran sehingga kualitas hasil belajar lebih optimal. Selain itu, peningkatan kompetensi pedagogik guru berdampak tidak langsung pada kemandirian belajar siswa, karena guru mampu menyusun pembelajaran yang mendorong partisipasi aktif dan pengelolaan belajar secara mandiri. Penelitian ini menegaskan bahwa kepemimpinan kepala sekolah dalam menumbuhkan budaya supervisi akademik berperan penting bagi pengembangan guru dan kemandirian belajar siswa. Kata kunci: Kepala sekolah; supervisi akademik; kompetensi pedagogik; kemandirian belajar.